OPTIMIZATION OF USE OF INDONESIA PORT INTEGRATION SYSTEM (INAPORTNET) IN SERVICE CLEARANCE IN AND CLEARANCE OUT BY THE OFFICE OF THE PORT AUTHORITY CLASS II PALEMBANG - Setiawan, Bambang; Melayu, Donny Afrizal; Komalasari, Yeti; Syera, Subriyan King (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
The Harbor Master’s Office of the Class II Palembang Port Authority is a technical implementing unit within The Ministry of Transportation in the waters of Palembang and its surroundings is under and directly responsible to the Director General of Sea Transportation. This study aims to determine the application of the use of the Indonesia Port Integration System (INAPORTNET) in service Clearance In And Clearance Outing the area of the Office of the Harbor Master of Class II Palembang Port Authority. This problem refers to Ministerial Regulation Number 93 of 2013 concerning the Organization and Business of Sea Transportation, Ministerial Regulation Number 93 of 2013 concerning the Organization of Business Related to Transportation in Waters, and Ministerial Regulation Number of 8 of 2022 concerning Procedures for Ship Service Through INAPORTNET. The result of the study are:1) Implementation of the use of Inaportnet by Office Harbor Master of Class II Palembang Port Authority in clearance services not optimal because there are obstacles in its implementation. 2) Obstacles faced by shipping company agencies and the Harbor Master’s Office of the Class II Palembang Port Authority in the use of Inaportnet in carrying out clearance services, including expired documents, lack of training and socialization, and weak internet network. 3) Efforts that can be made by the shipping company agency and the Palembang Class II Port Authority Harbor Master’s Office in dealing with obstacles that occur include extending expired certificates so that when uploading certificates to the system Inaportnet. There are no problems that could hinder the clearance process and socialization including training is carried out so that service users can Inaportnet do not feel confused in the stages of using the service Inaportnet can increase internet speed so that there are no problems related to the internet network when uploading data to the system.Inaportnet.